Ethics of Artificial Intelligence in Maqāṣid Al-Sharīa's Perspective - Habib, Zainal (Universitas Islam Negeri Madura, 2025)
The rapid development of Artificial Intelligence (AI) has brought significant transformation across various sectors but also presents complex and urgent ethical challenges. Key issues include algorithmic bias that may reinforce social discrimination, privacy violations due to massive data collection without adequate control, and unclear accountability in autonomous AI systems. These challenges threaten social justice, individual rights, and public trust in technology. This study aims to develop an AI ethics framework grounded in Maqāṣid al-Sharīʿa, the Islamic legal philosophy emphasizing the protection of five fundamental values: religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). A qualitative literature review method employing content analysis and thematic synthesis was applied to examine relevant literature on AI ethics and Maqāṣid al-Sharīʿa, identifying gaps and opportunities for normative integration. The findings demonstrate that Maqāṣid al-Sharīʿa offers a holistic perspective complementing Western AI ethics frameworks by incorporating spiritual, moral, and social justice dimensions. The principle of ḥifẓ al-ʿaql underpins efforts to combat misinformation, while ḥifẓ al-māl guides the equitable development of Sharia-compliant fintech. This study recommends inclusive algorithm design, Sharia-based regulation, and multidisciplinary collaboration among religious scholars, technology developers, and regulators to ensure ethical, responsible, and sustainable AI development.